Prevalence of Salmonella spp., Shigella spp., and intestinal parasites among food handlers working in University of Gondar student’s cafeteria, Northwest Ethiopia - Amare, Azanaw; Eshetie, Setegn; Kasew, Desie; Amare, Ayenew; Abebe, Wondwossen; Moges, Feleke (Frontiers in Public Health, 2024)
Background: Food-borne infections continue to be a major public health problem at the international level. The issue becomes more serious in developing countries like Ethiopia.Objective: This study aimed to examine the prevalence of Salmonella and Shigella species and intestinal parasites, as well as antimicrobial resistance patterns and associated factors among food handlers at the University of Gondar cafeteria in northwest Ethiopia Methods: An institutional-based cross-sectional study was conducted from February to June 2021 in the University of Gondar cafeterias. Data related to the socio-demographic characteristics and hygienic practices of study participants were collected using structured questionnaires. A total of 290 stool samples were collected from food handlers. Culture and conventional biochemical tests were used to isolate the Salmonella and the Shigella species. Wet mount, Formolether concentration, and Kato Katz techniques were applied to identify intestinal parasites. Additionally, drug susceptibility tests were performed using the disk diffusion method. Statistical analysis was done using SPSS version 26.Results: Of 290 food handlers' stool samples analyzed, Twenty-seven 27 (9.3%) were positive for both Salmonella and Shigella species. The prevalence of Salmonella and Shigella species was 16 (5.5%) and 11 (3.8%), respectively. Most of the isolated pathogens were resistant to tetracycline 19 (70.4%), and trimethoprim/sulphamethoxazole 19 (70.4%). The overall rate of multidrug resistant Shigella and Salmonella isolate was 59.3%. Besides, Fifty-seven 57(19.7 %) of the participants were positive for one or more intestinal parasites. The most prevalent intestinal Parasitosis was E. histolytica/dispar 22(7.6%), followed by G. lamblia 13(4.5%), and Ascaris lumbricoides 11(3.8 not washing hands after using the toilet (AOR: 4.42, 95% CI: 1.57, 10.56), and consuming unpasteurized milk (AOR: 3.14, 95% CI: 1.65, 3.96), were factors significantly associated with the prevalence of Salmonella, and Shigella infection. Similarly, not washing hands after using the toilet (AOR: 2.19, 95% CI: 1.0, 1.4), and consuming unpasteurized milk (AOR: 10.4, 95% CI: 3.8, 28.8), were factors significantly associated with the prevalence of intestinal parasites infectionThe prevalence of intestinal parasites, Salmonella, and Shigella species was high. Therefore, it is imperative to implement a public health policy that includes ongoing microbiological surveillance.